Somatization and health seeking behavior - Garala, Vishal; Brahmbhatt, Mehul; Shah, Hemang; Vankar, Ganpat (International Journal of Research in Medical Sciences, 2017)
Background:Somatization is the state of being symptomatic which is not explained medically associated with psychological distress and health-seeking behavior and is present in at least 10% to 15% in OPD. Methods:50 patients with long standing history of MUS were evaluated by using modified Bradford inventory. Results: Somatization was most common in younger age, female and lower socio-economical class. Feeling of weakness or lack of energy much of the time in both male and female respectively 94.7% and 96.7% are the most common symptomatic presentation in Somatization during last 2 years, although there were symptomatic differences in males and females. Severity of symptoms was higher among females. 13% of female pts had undergone hysterectomy due to persistent gynecological problems during course of illness. 82% pts had illness of more than 2 years. The mean duration of illness at the time of assessment was 6.8 years. Most of the patients had visited to multiple consultants and underwent many costly diagnostic procedures for their symptoms .Most of the patients after multiple investigations and consultations were not ready to accept psychological origin of their physical illness and continued to see next practitioner as they remained dissatisfied and distressed. One or more physical illness is the common explanation by physicians. Patients presented with somatization has an another diagnosis in significant cases like Major depressive disorder, anxiety disorder, alcohol use disorder. Conclusion:Somatization was common among female, but it was not uncommon in male. Patient suffering from somatization disorder has very high rate of health care utilization and they perceived themselves as severely ill and were willing to undergo multiple hospitalizations, diagnostic studies, and operations, remained dissatisfied. Need to strengthened consultation liaison between physician and psychiatrist.